Safety and Tolerability of Leucine Supplementation in Elderly Men. Issue 12 (9th November 2016) - Elango, Rajavel; Rasmussen, Betina; Madden, Kenneth
Abstract: Leucine, a branched-chain amino acid, has been shown to stimulate muscle protein synthesis and has been suggested to play a role in the prevention of age-related muscle atrophy (sarcopenia). Although leucine supplementation may be beneficial, the efficacious dose of leucine is unknown. Before conducting studies with increased doses of leucine, the Tolerable Upper Intake Level (UL) for leucine needs to be determined. The objective of this review is to describe 2 current studies to determine the UL for leucine in young and elderly men. Initially, in young men we tested the conceptual model of determining the maximum oxidative capacity of an amino acid to be an ideal marker for identifying the UL. Leucine oxidation, measured with the use of L-[1- 13 C]leucine, increased with increasing leucine intakes and reached a plateau at higher intakes. Two-phase linear regression analysis identified a breakpoint of 550 mg ⋅ kg −1 ⋅ d −1 (95% CI: 454, 646 mg ⋅ kg −1 ⋅ d −1 ), with a simultaneous increase in blood ammonia concentrations above normal values (35 μmol/L). Recently, a similar study was conducted in elderly men (∼72 y old). A breakpoint in leucine oxidation was observed at 431 mg ⋅ kg −1 ⋅ d −1 (95% CI: 351, 511 mg ⋅ kg −1 ⋅ d −1 ), with blood ammonia concentrations above normal (35 μmol/L) at leucine intakes >550 mg ⋅ kg −1 ⋅ d −1 . Taking the data together, the UL for leucine intake in healthy elderly men could be set at a value similar to young men, at 500 mg ⋅ kg −1 ⋅ d –1, or ∼35 g/d for an individual weighing 70 kg; or, as a cautious estimate, the leucine UL could also be considered as 351 mg ⋅ kg −1 ⋅ d −1 (the lower 95% CI), which would be ∼24.5 g/d for an elderly individual weighing 70 kg. These studies to determine the UL for leucine in humans are acute diet studies, and future studies with additional biomarkers and long-term supplementation of leucine will be necessary.